Analysis of Wildlife Diversity, Abundance, and Distribution in the Sekaroh Forest to Support Ecotourism Potential - Yamin, M.; Khairuddin, Khairuddin; Mertha, I Wayan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Sekaroh Forest Area in Jerowaru District, East Lombok Regency, possesses significant biodiversity potential that supports sustainable ecotourism and serves as an ecological buffer zone in the southeastern coastal region of Lombok Island. This study aimed to analyze the diversity, abundance, and distribution of fauna as a basis for environmental management and ecotourism development. The study was conducted across three habitat types, namely grassland, savanna, and plantation forest. The observed fauna included arthropods, reptiles, birds, and mammals, which were documented through surveys and field observations. The data were analyzed using diversity, abundance, dominance, distribution pattern, and inter-habitat similarity indices. The results revealed that the Sekaroh Forest Area exhibits relatively high faunal diversity, with distinct community characteristics in each habitat type. Savanna and plantation forest habitats had higher abundances of birds and arthropods than grassland habitats, whereas certain reptiles and mammals were found only in specific habitats. These findings indicate that the Sekaroh Forest Area has high ecological value and considerable ecotourism potential; therefore, it should be managed sustainably, with careful consideration of environmental conservation.